Estrés y depresión en mujeres con trabajo remunerado y amas de casa en tres barrios de Loja - Amay Guachizaca, Andrea Alexandra (2020)
For many years, the figure of housewife was associated with the woman who was dedicated exclusively to household chores. Today, it is common for women to take up jobs equivalent to those of men: this mean that they work in a paid way because of the modern lifestyle, women have inserted in the work’s world and becoming more vulnerable to stress and depression. Based on these considerations, it was planned to study two groups of women; those were paid workers and housewives. They were in the age range of 30 – 45 years which are residing in three neighborhoods of the city of Loja in 2018; in order to determine whether or not there are significant differences in stress and depression levels. It was applied the observational – analytical methodology; the sample was randomly made up of 420 women, 220 of whom had paid work and the other 200 housewives. The assessment of stress and depression levels was determined by the Beck Test and the Work Stress Test respectively. Among the main results it has been seen that women housewives are more likely to get depressed and less stressed in comparison to women with paid work. Concluding that the level of stress and depression is in close association with the activity that women carry out. Keywords: Beck Test, Work Stress Test, Domestic, Stipend.